Preconditioning of mesenchymal stem cells with ghrelin exerts superior cardioprotection in aged heart through boosting mitochondrial function and autophagy flux - Sun, Liqiang; Zhang, Wenlong (European journal of pharmacology, 2021)
Application of mesenchymal stem cells (MSCs) is considered as a promising cell-based therapy to induce cardioprotection against ischemia-reperfusion (IR) injury. Preconditioning of MSCs is the key strategy to improve MSCs functions in vitro and their efficacy in vivo, especially in elderly subjects in whom cardioprotection is lost. This study investigated the effects of preconditioning of human umbilical cord-derived MSCs with ghrelin and their combination with nicotinamide-mononucleotide (NMN) on cardioprotection, and the role of autophagy flux and mitochondrial function in aged hearts subjected to IR injury. Aged Sprague Dawley rats (20–22 months old) were subjected to LAD occlusion-induced myocardial IR injury and treated with ghrelin-preconditioned or unconditioned-MSCs at early reperfusion. NMN (500 mg/kg, i.p) was also administered at early reperfusion and repeated 12 h later. Intra-myocardial injection of ghrelin-preconditioned MSCs reduced infarct size and cardiotroponin release of aged myocardium, and improved cardiac function following IR injury. MSCs preconditioning with ghrelin restored IR-induced mitochondrial reactive oxygen species and membrane potential depolarization and enhanced ATP production. To reveal possible mechanism, preconditioned-MSCs increased autophagy flux by downregulating the overexpression of Beclin-1 and P62 proteins and increasing the LC3-II expression and LC3-II/LC3-I ratio. Moreover, combining NMN to ghrelin-preconditioned MSCs synergistically augmented its protective effects on infarct size and mitochondrial function. All above effects were abolished by autophagy flux inhibitor, chloroquine. Thus, ghrelin may serve as a promising candidate to improve the cardioprotective efficacy of MSC-based therapy via autophagy/mitochondrial pathway and that NMN serves as a good booster in combination therapy in aged hearts. •Preconditioning of MSCs with ghrelin improves their efficacy in cardioprotection in vivo.•Monotherapy-induced cardioprotection is usually lost in elderly patients with myocardial IR injury.•Ghrelin-preconditioned umbilical cord-derived MSCs restore loss of MSCs-induced cardioprotection in aging.•Combining ghrelin-preconditioned MSCs with NMN is a superior strategy in reducing infarct size in aging.•Promotion of autophagy flux and mitochondrial function mediates ghrelin-preconditioned MSCs-NMN combination effects.